Observation and interpretation of neutron origin prior to hard X rays and pinch in a hundred joules plasma focus device. (26th October 2017) - Jain, J.; Moreno, J.; Morales, D.; Davis, S.; Bora, B.; Avaria, G.; Inestrosa-Izurieta, M.J.; Soto, L.
Abstract: The temporal correlation between neutron and hard X-ray (HXR) emissions from a hundred joules plasma focus device (PF-400J) was studied. A method, time history analysis, to estimate the time of origin of neutrons with respect to HXRs is applied. In most of the discharges, it was found that neutrons are originated before HXRs in the axial direction and after HXRs in the radial direction. In some discharges, the time difference between HXRs and neutrons origin was found large enough, so that it can be interpreted that those neutrons would have been originated before the pinch. A qualitative discussion is conjectured to explain the experimental observations.